Effects of neratinib on health-related quality of life in women with HER2-positive early-stage breast cancer: longitudinal analyses from the randomized phase III ExteNET trial. (23rd January 2019) - Delaloge, S; Cella, D; Ye, Y; Buyse, M; Chan, A; Barrios, C H; Holmes, F A; Mansi, J; Iwata, H; Ejlertsen, B; Moy, B; Chia, S K L; et al.
Abstract: Background: We report longitudinal health-related quality-of-life (HRQoL) data from the international, randomized, double-blind, placebo-controlled phase III ExteNET study, which demonstrated an invasive disease-free survival benefit of extended adjuvant therapy with neratinib over placebo in human epidermal growth factor receptor-2-positive early-stage breast cancer. Patients and methods: Women ( N   =   2840) with early-stage HER2-positive breast cancer who had completed trastuzumab-based adjuvant therapy were randomly assigned to neratinib 240  mg/day or placebo for 12  months. HRQoL was an exploratory end point. Patients completed the Functional Assessment of Cancer Therapy–Breast (FACT-B) and EuroQol 5-Dimensions (EQ-5D) questionnaires at baseline and months 1, 3, 6, 9, and 12. Changes from baseline were compared using analysis of covariance with no imputation for missing values. Sensitivity analyses used alternative methods. Changes in HRQoL scores were regarded as clinically meaningful if they exceeded previously reported important differences (IDs). Results: Of the 2840 patients (intention-to-treat population), 2407 patients were evaluable for FACT-B (neratinib, N   =   1171; placebo, N   =   1236) and 2427 patients for EQ-5D (neratinib, N   =   1186; placebo, N   =   1241). Questionnaire completion rates exceeded 85%. Neratinib was associated with a decrease in global HRQoL scores at month 1 compared with placebo (adjusted mean differences: FACT-B total, –2.9 points; EQ-5D index, −0.02), after which between-group differences diminished at later time-points. Except for the FACT-B physical well-being (PWB) subscale at month 1; all between-group differences were less than reported IDs. The FACT-B breast cancer-specific subscale showed small improvements with neratinib at months 3–9, but all were less than IDs. Sensitivity analyses exploring missing data did not change the results. Conclusions: Extended adjuvant neratinib was associated with a transient, reversible decrease in HRQoL during the first month of treatment, possibly linked to treatment-related diarrhea. With the exception of the PWB subscale at month 1, all neratinib-related HRQoL changes did not reach clinically meaningful thresholds. ClinicalTrials.gov: NCT00878709.